Reinventing hierarchy and bureaucracy from the bureau to network organizations - Diefenbach, Thomas, 1965-; By, Rune Todnem (Research in the sociology of organizations ;, 2012)
This special volume brings together leading scholars in the field of organisation studies to reflect on the universal phenomena of hierarchy (vertical organisation of tasks) and bureaucracy (rule-bound execution of tasks). The result is a colourful kaleidoscope of thought-provoking, critical and refreshingly non-mainstream analysis of hierarchy and bureaucracy. The chapters range from minute accounts of a single case to broader historical analysis, from the 'classical' journal paper to essay-style elaborations. The first section provides fundamentals and historical accounts of bureaucracy, highlighting negative and positive effects of bureaucracy and a differentiated picture with some future outlook. The second section focuses on the analysis of organisational, cultural and socio-psychological aspects of hierarchy and bureaucracy by interrogating hierarchy in contemporary work via a new framework, exploring the cultural fantasy of hierarchy and sovereignty, and examining subordinates' challenges to organisational hierarchy. The final section comprises two chapters which provide some alternative views on, and alternatives to hierarchy. One is alarming, the other is puzzling.